Lights out! - Penner, Lucille Recht.frey50; Smath, Jerry (New York : Kane Press, 2000)
Hoping to be the last person awake, a young girl keeps count as one person after another turns out a light in the apartment building across from hers.
77488
Keywords: Bedtime -- Fiction; Subtraction -- Fiction